The Implementation of Google Classroom as a Medium of English Learning - Aga Kristyasa (English Education Department Slamet Riyadi University Surakarta, 2021)
Nowadays, learning process is carried out online. One of the popular platforms is Google Classroom. This research focused on the use of Google Classroom as a medium of English learning. The objectives of the research were: 1) to find out about the process of teaching learning using Google Classroom as a medium of English learning at the eighth grade of SMPN 1 Colomadu in 2020/2021 Academic Year.; 2) to find out about the benefits of using Google Classroom as a medium of English learning at the eighth grade of SMPN 1 Colomadu in 2020/2021 Academic Year.; 3) to describe the student's problems during the teaching-learning process using Google Classroom as a medium of English learning at the eighth grade of SMPN 1 Colomadu in 2020/2021 Academic Year. This was a descriptive qualitative research. The subject of this research was the students of class 8E consisting of 30 students of SMPN 1 Colomadu. The technique of collecting data was questionnaire distributed via Google form. The results of this research indicated that more than 81% of students using Google Classroom as a medium of interaction, discussion, and sharing their assignments and materials with other students or teachers went well. Almost all of the students had a positive response and the activities of using Google Classroom in English learning experienced the benefits of the Google Classroom. However, the students had some problems related with internet signal. Keywords; Google Classroom, Process, Benefits, Students Problems